Qualidade vocal em individuos asmáticos com e sem disfunção paradoxal de pregas vocais: correlatos perceptivo-auditivos, acusticos e fisiologicos - Cukier, Sabrina (2006)
Objective: investigating the perceptual, acoustic and physiological vocal quality of a group of asthmatic individuals with paradoxical vocal fold dysfunction (PVFD) in relation to a group of asthmatic individuals without PVFD and a group of individuals without breathing problems. Methods: recording of acoustic and electroglottographic speech data from 9 individuals with PVFD, 8 with asthma without PVFD and 8 without breathing problems (control group). The perceptual analysis was carried out by means of the phonetic vocal quality analysis protocol. The acoustic analysis comprised both long and short term spectra. The Lx wave of the electroglottographic signals were analyzed and measures relative to the phases of the glottal cycle were extracted. Results: Both PVFD and asthma groups presented supralaryngeal settings characterized by smaller extension and higher constriction of the vocal tract. Laryngeal settings of both PVFD and asthma groups were found to be characterized by hyperfunction, creaky voice, rough voice, breathy voice, sonority breaks, diplophonia and instability, with higher frequency of occurrence of rough voice and breathy voice adjustments and short term instability events in the asthma group. The analysis of the long term spectrum declination lines made it possible to differentiate among the groups and genders: higher degree of spectral intensity was found in the feminine asthma and the masculine control groups and higher degree of spectral intensity in the PVFD group, differentiation also brought out by intensity measures of short and long term spectra. The inspection of the Lx wave revealed the asthma and PVFD groups differed from the control group due to the presence of noise, low intensity and prolonged closed phases. The electroglottographic measures related to speed index and contact coefficient area differentiated the asthma and PVFD groups. Conclusions: the analysis of the data corroborates the hypothesis of the presence of vocal alteration in patients with PVFD and in patients with asthma and favors the description of vocal quality as a diagnosis method, delineating the important demand of speech therapy treatment for these patients